A comprehensive review of artificial intelligence for pharmacology research - Li, Bing; Tan, Kan; Lao, Angelyn R.; Wang, Haiying; Zheng, Huiru; Zhang, Le (Frontiers in Genetics, 2024)
With the innovation and advancement of artificial intelligence, more and more artificial intelligence techniques are employed in drug research, biomedical frontier research, and clinical medicine practice, especially, in the field of pharmacology research. Thus, this review focuses on the applications of artificial intelligence in drug discovery, compound pharmacokinetic prediction, and clinical pharmacology. We briefly introduced the basic knowledge and development of artificial intelligence, presented a comprehensive review, and then summarized the latest studies and discussed the strengths and limitations of artificial intelligence models. Additionally, we highlighted several important studies and pointed out possible research directions.